High-efficient production of fructo-oligosaccharides from inulin by a two-stage bioprocess using an engineered Yarrowia lipolytica strain. (1st October 2017) - Han, Yao-Zu; Zhou, Chao-Chao; Xu, Yan-Yan; Yao, Jing-Xin; Chi, Zhe; Chi, Zhen-Ming; Liu, Guang-Lei
Highlights: A convenient and efficient two-stage bioprocess for FOSs production was proposed. An optimized endo-inulinase gene was overexpressed in Y. lipolytica . A yield of 0.91 gFOS /gInulin was achieved with a productivity of 15.18 g/L/h. Abstract: A convenient and efficient two-stage bioprocess was established for fructo-oligosaccharides (FOSs) production, during which the endo-inulinase was first produced and subsequently the inulin supplemented was directly hydrolyzed by the produced endo-inulinase, in the meantime the generated non-prebiotic saccharides was assimilated by the yeast cells. This process was implemented by an engineered Yarrowia lipolytica strain Enop56, in which an optimized endo-inulinase gene from Aspergillus niger was overexpressed. When the strain Enop56 was fermented with an inulin concentration of 600 g/L in a 10-L bioreactor, the inulinase activity, FOSs titer, yield and productivity reached to 551.6 U/mL, 546.6 g/L, 0.91 gFOS /gInulin, and 15.18 g/L/h, respectively. Besides, the hydrolysis products were mainly FOSs with polymerization degrees of 3–5 and the total amount of non-prebiotic mono- and disaccharides was only 4.97% in the final fermentation broth. This study demonstrated that the two-stage bioprocess using the strain Enop56 was a promising strategy to produce FOSs on an industrial scale.